The core triacylglycerol toolbox in woody oil plants reveals targets for oil production bioengineering - Cao, Yunpeng; Li, Qiang; Zhang, Lin (Frontiers in Plant Science, 2023)
Woody oil plants are the most productive oil-bearing species that produce seeds with high levels of valuable triacylglycerols (TAGs). TAGs and their derivatives are the raw materials for many macromolecular bio-based products, such as nylon precursors, and biomass diesel. Here, we identified 280 genes encoding seven distinct classes of enzymes (i.e., G3PAT, LPAAT, PAP, DGAT, PDCT, PDAT and CPT) involved in TAGs-biosynthesis. Several multigene families are expanded by the large-scale duplication events, such as G3PATs, and PAPs. RNA-seq was used to survey the expression profiles of these TAG pathway-related genes in different tissues or development, indicating functional redundancy for some duplicated genes originated from the large-scale duplication events, and neo-functionalization or sub-functionalization for some of them. Sixty-two genes showed strong, preferential expression during the period of rapid seed lipid synthesis, suggesting that their might represented the core TAG-toolbox. We also revealed for the first time that there is no PDCT pathway in Vernicia fordii and Xanthoceras sorbifolium. The identification of key genes involved in lipid biosynthesis will be the foundation to plan strategies to develop woody oil plant varieties with enhanced processing properties and high oil content.